Determinants of entrepreneurial intention among business students in Indonesia - Sahban, Muhammad Amsal (2016)
In the world of entrepreneurship, the fundamental aspect that needs to be embedded in every business starter or business graduate is an entrepreneurial intention. Entrepreneurial intention is very much required in Indonesia, given the number of entrepreneurs today is less than 2% compared to other neighboring countries, like Singapore, Malaysia, Thailand and even Vietnam. Moreover, there are only 17% of university graduates in Indonesia who are interested in entrepreneurship. This is due to the fact that the entrepreneurial career is not considered as an important career in Indonesia. Despite several entrepreneurial programs initiated to nurture a business mentality and awareness for the business students, it does not make a significant change in their entrepreneurial behavior. Many of them do not have enough courage to deal with entrepreneurship. It is because the entrepreneurial orientation of the business students is very weak, and there is a lack of self-efficacy to perform the business tasks. In addition, there is seldom any support from their parents and peer groups to make them motivated enough to initiate a business. The entrepreneurship programs like internship program and business incubation program in higher education institutions have failed to enhance the entrepreneurial spirit among business students. These entrepreneurship programs have not been implemented as it should be and desperately need more improvement. Hence, the main purpose of this study is to investigate the determinants of entrepreneurial intention among students in the economics and business faculty in Indonesia’s higher education institutions by determining the direct factors affecting entrepreneurial intention. By employing convenience sampling, a total of 381 questionnaires were successfully distributed to the business students and could be used for this study. The usable questionnaires were examined by employing structural equation modeling (SEM). This study found that five predictors are significant factors with respect to entrepreneurial intention: entrepreneurial orientation, social support, entrepreneurial self-efficacy, entrepreneurial internship program and business incubation program. To sum up, these factors of entrepreneurial intention are found to be essential elements for students to successfully start a business and contribute to increasing the number of young entrepreneurs in Indonesia